2016
DOI: 10.1186/s40792-016-0267-x
|View full text |Cite
|
Sign up to set email alerts
|

A case of acute myocardial infarction due to cardiovascular syphilis with aortic regurgitation and bilateral coronary ostial stenosis

Abstract: We report an interesting case of a 66-year-old man with acute myocardial infarction (AMI) with bilateral coronary ostial stenosis cardiovascular syphilis complicated by aortic regurgitation (AR). A 12-lead electrocardiogram and blood tests on arrival suggested AMI, and echocardiography showed moderate AR. Emergency coronary angiography showed bilateral coronary ostial stenosis. The patient underwent emergency surgical treatment, coronary artery bypass grafting, and aortic valve replacement with a bioprosthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…[ 12 ] For AMI caused by cardiovascular syphilis lesions, Mutsuo Tanaka et al reported the use of CABG to treat cardiovascular syphilis complicated with aortic valve insufficiency and bilateral coronary artery stenosis caused by AMI. [ 13 ] Predescu et al reported that emergency PCI can be used to treat patients with acute anterior myocardial infarction caused by severe left coronary artery stenosis secondary to syphilitic aortitis. [ 5 ] For non-atherosclerotic lesions, percutaneous transluminal coronary angioplasty with stents is a safe and effective replacement for CABG.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] For AMI caused by cardiovascular syphilis lesions, Mutsuo Tanaka et al reported the use of CABG to treat cardiovascular syphilis complicated with aortic valve insufficiency and bilateral coronary artery stenosis caused by AMI. [ 13 ] Predescu et al reported that emergency PCI can be used to treat patients with acute anterior myocardial infarction caused by severe left coronary artery stenosis secondary to syphilitic aortitis. [ 5 ] For non-atherosclerotic lesions, percutaneous transluminal coronary angioplasty with stents is a safe and effective replacement for CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Because this pathology occurs in patients with no history of cardiovascular diseases or risk factors, the diagnosis is generally late, leading to irreversible damage such as extended myocardial infarction, 2 severe aortic insufficiency with a dilated ventricle, cardiac failure and giant aneurysms that could be sacciform with regional erosion in vertebral bodies, rib, sternum, vena cava, and skin. 3,4 Owing to intense scarring of the media layer, aortic dissection is highly unlikely to occur.…”
Section: Introductionmentioning
confidence: 99%
“…Penicillin has been the first line of therapy for treatment of syphilis [1]. There is no standardized treatment for coronary ostial stenosis, and coronary artery bypass grafting has been regarded as an effective treatment in recent years [4]. However, as in our case and in the literature [5], PTCA with stenting is an additional treatment choice cc This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/bync/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.…”
Section: Syphilic Aortitismentioning
confidence: 99%